Ten Old Babylonian Mathematical Problems from Tell Haddad, Himrin - al-Rawi, Farouk N. H.
ersch. 1987; F?r?q N??ir al-R?w?; Haddad 104 (copy, photo) found in room 10, area 2, stratum 3 at Tell Haddad together with texts that exhibit date formulas of Daduša and ?illi-Sîn.